2018
DOI: 10.4038/sljpsyc.v9i1.8174
|View full text |Cite
|
Sign up to set email alerts
|

Stigma due to their work in mental health, among mental health professionals in Sri Lanka

Abstract: Background Stigma related to mental health is not limited to individuals with mental illness or their families; health professionals working in mental health are also affected by it. Stigma among mental health professionals may lead to lack of work satisfaction, and poor recruitment and retention of personnel in the mental health sector resulting in poor mental health care. Stigma among the health professionals in Sri Lanka has not been studied adequately. Aims To study the extent, nature and correlates of sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Many studies report cultural factors to be a barrier to help-seeking behaviors (Rostain et al, 2015), which are ultimately related to the extent to which a service provider will be able to function to the fullest of their capabilities. Studies conducted in SL divulge that stigma surrounding the topic of MH often prevents service providers from accessing those in need (Samarasekara et al, 2012) and that MH professionals themselves were stigmatized and alienated by their communities, corroborating the fear of the "title" and the active discouragement of help seeking the counsellors in this study spoke about (Liyanage et al, 2018).…”
Section: Discussionsupporting
confidence: 71%
“…Many studies report cultural factors to be a barrier to help-seeking behaviors (Rostain et al, 2015), which are ultimately related to the extent to which a service provider will be able to function to the fullest of their capabilities. Studies conducted in SL divulge that stigma surrounding the topic of MH often prevents service providers from accessing those in need (Samarasekara et al, 2012) and that MH professionals themselves were stigmatized and alienated by their communities, corroborating the fear of the "title" and the active discouragement of help seeking the counsellors in this study spoke about (Liyanage et al, 2018).…”
Section: Discussionsupporting
confidence: 71%
“…Lack of staff and higher number of patients which elevates the number of shift duties especially night shift duties, physical arrangement of the hospitals where easy access for patients' relatives and outsiders to the working units and more female employment within the nursing profession are some of the contributing factors for this higher number of WPV incidence in Sri Lanka. A study conducted by Liyanage, Hewawitharana, De Silva, & Dissanayake (2018) in Sri Lanka revealed that, 58% were reported of being either attacked or threatened with physical violence at the workplace. When considering the type of violence, verbal violence was identified as the most common type (87.8%), followed by emotional violence (64.9%), physical violence (15.1%), sexual violence (3.8%) and racial harassment (2.1%).…”
Section: Discussionmentioning
confidence: 99%
“…As in the general population, health professionals also frequently have negative attitudes. A study showed that the majority of Sri Lankan doctors and medical students believed patients with mental illness are dangerous, unpredictable and difficult to communicate with, and that they perceive the world differently (Liyanage, Rowel, Hewawitharana, Silva & Dissanayake, 2018).…”
Section: Discussionmentioning
confidence: 99%